Proceedings of the 1996 Multicultural Marketing Conference - Choudhury, Pravat K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume includes the full proceedings from the 1996 Multicultural Marketing Conference presented by the Academy of Marketing Science (AMS) and Old Dominion University in Virginia Beach, Virginia. The focus of the conference and the enclosed papers is on marketing to various ethnic groups in both a US and global context. It presents papers on various multicultural issues across the entire spectrum of marketing activities and functions including marketing management, marketing strategy, and consumer behavior. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy’s flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.
Creating Brand Names: Strategic and International Considerations -- Consumer Behavior in East/West Cultures -- Intercultural Communication within Multinational Marketing Firms -- Antecedents of Marketing Adoption -- Empirical Investigation of the Determinants of Marketing Sarawak’s Heritage as a Tourist Destination -- Are Perceptions of Personal Selling the Same in Singapore as Those in the U.S.? -- Purchasing Decisions Among Black and White Families for Selected Products in Durham, North Carolina -- Psychological Influences on African American Compulsive Gambling Behavior -- Ethnicity and Lottery Ticket Purchase -- Ethnocentric Tendencies and Consumer Purchase Behavior in Central and Eastern Europe -- Cultural Differences in the Appreciation of Art Periods and Art Forms -- Consumers’ Perceptions of Uni- and Bi-National Products -- An Examination of the Impact of Closing Techniques and Buyer Gender on Attitude Toward the Salesperson -- Training Multicultural Sales Managers -- How Appealing are Sales Careers? -- Impact of Shortening International Product Life Cycle -- Religion: The Determining Factor in Constructing Global Marketing Strategies -- A Study of Employee Satisfaction with HMO Services at a Historically Black University -- Predictive Factors of Abortion Attitudes Between Whites and Blacks -- Health Care: A Competitive Environment -- Malaysian Consumers Attitudes and Purchases Toward Local vs. Foreign Made Products -- Wives’ Involvement and the Effects of Sex Role Orientation in Purchase Decisions by Families -- Consumer Attitudes Toward Advertising: Does Culture Matter? -- International Advertising: Using Hofstede’s (1980) Framework as a Basis for Standardization.
Keywords: Marketing; Leadership; Sales management; Marketing; Business Strategy/Leadership.; Sales/Distribution.